STRATEGI PEMASARAN DALAM MENINGKATKAN PEMBIAYAAN MITRA GUNA ONLINE DI BSI KCP LUBUK SIKAPING - Muhammad Ridwan; Tartila Devy (Adisam Publisher, 2025)
Mitraguna is a product of Bank Syariah Indonesia KCP Lubuk Sikaping, an online financing service. On the other hand, not everyone in Lubuk Sikaping is keen on utilizing the Mitraguna online loan service. The fact that very few clients actually use Mitraguna's online financing is the main issue with this research. Among other things, this is because some clients still have plenty of money in their pockets and don't require the loan. The result is that the Mitraguna online finance goal is not met by BSI KCP Lubuk Sikaping. Qualitative research methodologies were used in this study. Data collecting approaches by conducting observations, interviews and documentation. This study's findings reveal that Bank Syariah Indonesia KCP Lubuk Sikaping's marketing strategy for their Mitraguna online financing product follows the 9Ps of marketing: product, price, place, promotion, people, physical evidence, process, packaging, and public relations). Challenges include: 1) the community's lack of familiarity with Islamic banks and online partner funding, and 2) the necessity of going via Bank Syariah Indonesia's payroll system.